The impact of time to treatment initiation on survival from head and neck cancer in north-eastern Italy. (April 2017) - Polesel, Jerry; Furlan, Carlo; Birri, Silvia; Giacomarra, Vittorio; Vaccher, Emanuela; Grando, Giuseppe; Gobitti, Carlo; Navarria, Federico; Schioppa, Ornella; Minatel, Emilio; Bidoli, Ettore; Barzan, Luigi; et al.
Highlights: Treatment delay is associated to a worse prognosis in head & neck cancer patients. Treatment initiation within 45 days from diagnosis is auspicable. Early-stage cancers undergoing surgery suffer the most from treatment delay. Care transition to specialized centers should be eased to improve prognosis. Abstract: Objectives: To evaluate the impact of time to treatment initiation (TTI) on overall survival in patients with head-and-neck squamous cell carcinoma (HNSCC). Materials and methods: In the period 2003–2009, 1616 HNSCC patients were diagnosed in Friuli Venezia Giulia Region, Northeastern Italy, including 462 oral, 346 oropharyngeal, 212 hypopharyngeal, and 596 laryngeal cancers. Clinical information, including date and type of first treatment, and follow-up were retrieved from the regional Cancer Registry and a population-based health database collecting comprehensive health information on people living in the Region. Multivariate hazard ratio (HR) and confidence intervals (CI) were calculated through Cox model. Results: Overall, the median TTI was 28 days, (Q1-Q3: 13–45 days), but significant variations emerged according to anatomical site, cancer stage, treatment approach, and care transition to specialized centers. Five-year overall survival decreased with increasing treatment delay from 62% for TTI < 30 days to 39% for TTI ≥ 90 days (p < 0.01). HR of death was 1.13 (95% CI: 0.92–1.39) for TTI between 45–89 days, and 1.47 (1.05–2.05) for TTI ≥ 90 days. The association between TTI and poor prognosis was stronger for laryngeal cancers and early-stage HNSCCs. Further, care transition from community hospitals to specialized centers was associated to a better prognosis (HR = 0.73; 95% CI: 0.60–0.88). Conclusion: Our study findings suggest that HNSCC patients treated within 45 days from diagnosis have increased survival probabilities and that early-stage patients suffered the most from treatment delay. Furthermore, care transition to specialized centers –though competitive to timely treatment– improves survival by providing the most innovative technologies and treatment approaches.